A method of packaging molecule/cell-patterns in an open space into a glass microfluidic channel by combining pressure-based low/room temperature bonding and fluorosilane patterning. Issue 81 (28th September 2017) - Funano, Shun-ichi; Ota, Nobutoshi; Sato, Asako; Tanaka, Yo
Abstract : A fabrication method of a "post-molecule/cell patterned" glass microchip was developed by pressure-based bonding and patterning with a fluorosilane coupling reagent. Abstract : We report a fabrication method of a "post-molecule/cell patterned" glass microchip using pressure-based low/room temperature bonding in dry conditions combined with fluorosilane patterning. Multiple proteins/cells were patterned in a single channel using this method. This simple method will provide benefits for using microchips for high throughput analysis in many biological experiments.